Empowering Church Youth Through AI Literacy for Digital Career Readiness - Erikson Damanik; Edo Maranata Tambunan; Meylida Girsang; Khansa Khalishah; Toras Pangindoan Batubara; Musthafha Haris Munandar; Hengki Mangiring Parulian Simarmata (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
The development of digital technology, especially artificial intelligence (AI), has had a significant impact on the world of work, requiring the younger generation to have qualified technological literacy. However, church youth often face limited access to information and technology-based training. This Community Service Activity (PKM) aims to increase technology literacy and basic understanding of AI for the youth of the HKBP Bethesda Perumnas Mandala Church as an effort to prepare for career readiness in the digital era. The implementation method is in the form of an interactive workshop that includes the delivery of materials, discussions, and questions and answers involving 75 participants of productive age. The results of the activity showed a significant increase in participants' understanding of AI concepts, ethics in the use of technology, and strategies for dealing with digital-based career opportunities. The active discussion of the participants showed enthusiasm and readiness to adapt to technological transformation. This activity proves that collaboration between universities and churches is effective in strengthening the digital capacity of the younger generation, and can be a model of sustainable empowerment in the religious community.